Wayside School gets a little stranger - Sachar, Louis; Schick, Joel (New York : Avon Books, 1995)
Unusual things continue to happen in the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
Keywords: Schools; Humorous stories